2014
DOI: 10.4149/neo_2014_042
|View full text |Cite
|
Sign up to set email alerts
|

Pathological analysis of extracapsular extension of metastatic lymph node and its potential impact on nodal clinical target volume in the radiotherapy of esophageal squamous cell carcinoma

Abstract: There is no consensus regarding the clinical target volume (CTV) margins which surround the gross tumor volume of metastatic lymph nodes (LN) in radiotherapy of esophageal squamous cell carcinoma (ESCC). This study retrospectively assessed the distance of extracapsular extension (ECE) of metastatic LN in thoracic ESCC and defined nodal CTV margins. Histological sections of metastatic LNs from 217 patients with thoracic ESCC were re-examined. The incidence and maximal distance of ECE of metastatic LNs were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“… 9 , 10 It refers to the pathological positive area of LN which is considered as being closely related to the outcome of patients. 11 13 But there is still controversy about which LN stations should be included in treatment planning. 14 17 The LN stations of 101, 104-R, 105, 106rec-L, 106tb-L, 106tb-R, 107, 108, 110, 112, 2, 3, and 7 are generally considered as high-risk regions and are commonly included in treatment planning in thoracic ESCC.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 It refers to the pathological positive area of LN which is considered as being closely related to the outcome of patients. 11 13 But there is still controversy about which LN stations should be included in treatment planning. 14 17 The LN stations of 101, 104-R, 105, 106rec-L, 106tb-L, 106tb-R, 107, 108, 110, 112, 2, 3, and 7 are generally considered as high-risk regions and are commonly included in treatment planning in thoracic ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. ( 23 ) assessed 217 individuals with ESCC, and proposed a margin of 3.0–5.0 mm from GTVn to CTVn in order to include 95% of the extracapsular extension of lymph node, which depends on the diameter of the lymph node. CTVn provided a 0.5- to 1.0-cm radial margin around the GTVn to include the area of subclinical involvement in the NEOCRTEC5010 trial ( 5 ).…”
Section: The Details Of Target Volume Delineationmentioning
confidence: 99%
“…Table S2) [27]. Wang et al evaluated 217 patients with a squamous cell carcinoma, and suggested a margin of 0.3-0.5 cm from GTVn to CTVn to encompass 95% of the extracapsular extension, depending on the diameter of the lymph node [28].…”
Section: Literature Reviewmentioning
confidence: 99%